A review: Conversion of bioglycerol into 1,3-propanediol via biological and chemical method - Lee, C.S.; Aroua, Mohamed Kheireddine; Daud, Wan Mohd Ashri Wan; Cognet, P.; Peres-Lucchese, Y.; Fabre, P.L.; Reynes, O.; Latapie, L. (Elsevier, 2015)
Today, the price of glycerol has dramatically dropped due to its oversupply from biodiesel production as well as oleochemical industry. Thus, it is essential to develop processes to transform bioglycerol into commercially valued products which is important to ensure sustainability in the biodiesel and oleochemical industries. One possibility is to transform it in propanediols, which have numerous applications such as food additives, raw material in pharmaceutical and cosmetic industries. In this paper, methods of conversion of glycerol into 1,3-propanediol are reviewed and discussed in detail. (C) 2014 Elsevier Ltd. All rights reserved.